2014
DOI: 10.1371/journal.pone.0096228
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling Implies New Markers of Chemoresistance of Triple-Negative Breast Cancer

Abstract: ObjectiveTriple-negative breast cancer (TNBC) patients with truly chemosensitive disease still represent a minority among all TNBC patients. The aim of the present study is to identify microRNAs (miRNAs) that correlate with TNBC chemoresistance.MethodsIn this study, we conducted miRNAs profile comparison between triple-negative breast cancer (TNBCs) and normal breast tissues by microRNA array. Quantitative real-time PCR (qRT-PCR) was utilized to confirm the specific deregulated miRNAs change trend. We used sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 40 publications
8
129
0
1
Order By: Relevance
“…Upregulation of miR-181a expression was found in TNBC by three independent research groups where the increased expression of miR-181a correlated with breast cancer aggressiveness [24, 26, 45] (Table 1). Bisso et al investigated the expression of miR-181a in a panel of 104 primary breast cancers and eight normal tissue counterparts.…”
Section: Oncomir Activities Of Mir-181amentioning
confidence: 99%
“…Upregulation of miR-181a expression was found in TNBC by three independent research groups where the increased expression of miR-181a correlated with breast cancer aggressiveness [24, 26, 45] (Table 1). Bisso et al investigated the expression of miR-181a in a panel of 104 primary breast cancers and eight normal tissue counterparts.…”
Section: Oncomir Activities Of Mir-181amentioning
confidence: 99%
“…Both miR-205 and miR-342 have been proposed as potential biomarkers for diagnosis of TNBC (35). It has been previously shown that miR125b expression is lower in TNBC tumor tissue when compared with adjacent normal tissue, and has been related with chemoresistance (36). Finally, miR-345 expression was downregulated in ER À breast cancer patients, whereas miR-18a was increased (37).…”
Section: Mirna Expression Analysismentioning
confidence: 99%
“…miR-374b-5p contributes to gastric cancer cell metastasis and invasion via inhibition of RECK expression (19). miR-181a-5p is elevated in triple negative breast cancer and associates with chemoresistance (20). It is also upregulated in gastric cancer, with positive correlation with lymph node invasion, nerve invasion and vascular invasion (21).…”
Section: Resultsmentioning
confidence: 99%